Implementasi Model Pembelajaran Multikultural Untuk Meningkatkan Kompetensi Mahasiswa (Studi Pada Mahasiswa PGMI di IAIN Salatiga) - Rasimin, Rasimin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
Theoretically, multicultural education is a concept of education that provides equal opportunity regardless of gender, class, ethnic, racial, religious, and cultural background of learners. The learning model is carried out by stages: self-exploration studies, exploratory presentation, peer group analysis, expert opinion, and reflection. This study aims to improve the competence of mastery of IPS educational materials through multicultural learning model. The research findings show that the implementation of multicultural learning model can improve the competence of mastery of IPS Education materials for PGMI students at IAIN Salatiga. This is evidenced in the average class pre cycle activity of 60.25; Cycle I of 77.87 and in the second cycle of 82.22. Based on the analysis it is concluded that the implication of multicultural learning model can significantly improve student competence.